Acculturation of Expatriate Consumers: Conditional Effects of Mental Attachments to Home Country. Issue 3 (26th May 2020) - Miocevic, Dario; Zdravkovic, Srdan
Abstract: In this paper authors explore insufficiently addressed acculturation behaviors of expatriates. Based on the consumer acculturation literature and congruity theory, authors explore how expatriate's acculturation behaviors steer consumer's propensity to buy local food brands under conditional effects of mental attachments to home country. In order to test the proposed model a survey was conducted among 212 expatriates from developed economies living in the Greater Middle East. Study shows that expatriate consumers' acculturation will lead to higher propensity for buying local food brands when: 1) they perceive higher similarity between their home and host country retail system attributes and 2) locally produced food brand's perceived value is equal or better than the perceived value of food brands from expatriates' home country.